(untitled) (Research, Society and Development, 2021)
Hereditary angioedema (HAE) is a rare genetic disease characterized by recurrent cutaneous angioedema, severe abdominal pain, and airway compromise. This study aimed to describe the clinical profile of patients with HAE treated at the Clinic of Clinical Immunology and Allergy of a university hospital in the city of Maceió, Alagoas, Brazil. This is a retrospective, cross-sectional and descriptive study, where data such as sex, age at onset of HAE, manifestations, triggering factors, prophylactic therapy and crisis therapy were collected. Thirteen participants formed the total sample, eight male and aged between 08 and 40 years. Main triggering factor for trauma, with edema in the extremities being the most frequent sign. Tranexemic acid was the drug referred to as a therapeutic agent in times of crisis. The family history factor was present in 69.2% of the participants and, even though tranaxemic acid is not recommended for long-term prophylaxis for HAE, it is still a reference among the patients in this study, revealing the need to disseminate knowledge about the pathophysiological aspects of disease processes directed at health teams, in order to guide adequate therapy and, thus, reduce morbidity and mortality, ensuring a better quality of life for patients, as well as their families.